Dry - Shusterman, Neal; Shusterman, Jarrod ([New York, NY] : Simon & Schuster, 2018)
When the California drought escalates to catastrophic proportions, one teen is forced to make life and death decisions for her family in this harrowing story of survival from New York Times bestselling author Neal Shusterman and Jarrod Shusterman. The drought--or the Tap- Out, as everyone calls it--has been going on for a while now. Everyones lives have become an endless list of donts: dont water the lawn, dont fill up your pool, dont take long showers. Until the taps run dry. Suddenly, Alyssas quiet suburban street spirals into a warzone of desperation; neighbors and families turned against each other on the hunt for water. And when her parents dont return and her life--and the life of her brother--is threatened, Alyssa has to make impossible choices if shes going to survive.
Keywords: Droughts -- Juvenile fiction; Survival -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Conduct of life -- Juvenile fiction; Droughts -- Fiction; Brothers and sisters -- Fiction; Conduct of life -- Fiction; California -- Juvenile fiction; California -- Fiction; Science fiction; Audiobooks